BEHAVIORAL ECONOMICS AND ECONOMIC COMMUNICATION: ANALYZING THE IMPACT OF COGNITIVE BIASES ON DECISION-MAKING - Kosasih Kosasih; Pandu Lesmana; Loso Judijanto; Myra Cahyati; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Behavioral economics, a dynamic field at the intersection of psychology and economics, recognizes that human decision-making is far from the rational, utility- maximizing model traditionally assumed in economic theory. This study delves into the profound implications of cognitive biases on decision-making and explores how effective economic communication can mitigate their effects. Key findings reveal the prevalence of cognitive biases, including confirmation bias, anchoring, and loss aversion, impacting a majority of decision-makers. These biases significantly affect personal finance, investment, and public policy choices. Effective communication strategies, message framing, and behavioral insights are pivotal in countering these biases and improving decision quality. Armed with an understanding of cognitive biases, economic experts and policymakers can tailor communication and policy design to promote rational choices. The study also identifies challenges and future directions, emphasizing the ongoing need for research and innovative strategies. In conclusion, this research sheds Light on the interplay between cognitive biases, economic communication, and decision-making, offering insights into strategies for enhancing economic well-being and promoting informed choices.